Communication Ethical Problems of MTs Darul Ulum Students Tulang Bawang Barat in Learning Creed and Morals in The Digital Era - Nur Rohman Utsman; Mispani Mispani; Siti Roudhotul Jannah (CV. Bimbingan Belajar Assyfa, 2026)
This study aims to analyze the problems of students' communication ethics at MTs Darul Ulum Tulang Bawang Barat in Akidah Akhlak learning in the digital era, to identify the influencing factors, and to examine the role of Akidah Akhlak learning in shaping students' communication ethics. This study employs a qualitative approach with a case study method. Data were collected through observation, in-depth interviews, and documentation, involving students, teachers, and parents as informants. The data were analyzed through the processes of data reduction, data display, and systematic conclusion drawing. The findings reveal that the problems of students' communication ethics in the digital era are quite complex. The issues include the use of impolite language on social media, a lack of awareness of the impact of digital communication, and misunderstandings caused by indirect communication. The influencing factors include digital media as the dominant factor, family environment, peer environment, and students' level of understanding of Islamic communication ethics. Akidah Akhlak learning plays a strategic role in shaping students' communication ethics through the internalization of moral values, teacher role modeling, and the habituation of good behavior in the pesantren environment. The integration between classroom learning and boarding school guidance has proven to improve students' awareness in maintaining ethical communication, although it still requires continuous reinforcement. Therefore, strengthening communication ethics education based on Islamic values that are contextual to digital development is essential in forming students with noble character.